Subcellular Journey of Rare Cold Inducible 2 Protein in Plant Under Stressful Condition - Kim, Hyun-Sung; Park, Won; Lee, Hyeon-Sook; Shin, Jung-Ho; Ahn, Sung-Ju (Frontiers in Plant Science, 2021)
Rare cold inducible 2 (RCI2) proteins are small hydrophobic membrane proteins in plants, and it has been widely reported that RCI2 expressions are dramatically induced by salt, cold, and drought stresses in many species. The RCI2 proteins have been shown to regulate plasma membrane (PM) potential and enhance abiotic stress tolerance when over-expressed in plants. RCI2 protein structures contain two transmembrane domains that are thought to be PM intrinsic proteins and have been observed at the PM and endomembranes. However, cellular trafficking of RCI2s are not fully understood. In this review, we discussed i) general properties of RCI2s characterized in many species, ii) the uses of RCI2s as a tracer in live cell imaging analyses and when they are fused to fluorescence proteins during investigations into vesicle trafficking; iii) RCI2 functionalities such as their involvement in rapid diffusion, endocytosis, and protein interactions. Consequently, the connection between physiological characteristics of RCI2s and traffic of RCI2s interacting membrane proteins might be helpful to understand role of RCI2s contributing abiotic stresses tolerance.